Incidence Trends of Cervical Cancer and Its Precancerous Lesions in Women of Central Switzerland from 2000 until 2014 - Ochs, Katrin; Meili, Gesine; Diebold, Joachim; Arndt, Volker; Günthert, Andreas (Frontiers in Medicine, 2018)
Objective Cervical cancer (CC) screening by Pap smears has led to a decrease in the incidence of CC worldwide. Indeed, the incidence of CC in Switzerland is very low; however, there is a lack of data to evaluate the efficiency of the Pap smear as a screening tool. Until now, only Pap smears have been used and other methods such as the presence of an infection with HPV have not been integrated into the routine screening. The aim of this study is to evaluate trends in the incidence of CC and its precancerous lesions in Central Switzerland, which represents a rural region, with those in urban regions and the entire country of Switzerland. Methods All conizations and CC registered between 2000 and 2014 at the Institute of Pathology at the Cantonal Hospital of Lucerne have been included in our study. The incidence of CC and its precancerous lesions have been categorized according to age, stage, morphology, and study period. Age-standardized incidence in the Canton of Zurich and the entire country served as reference for the assessment of trends in CC incidence in the study region. Results In Central Switzerland, the number of conizations performed annually has more than doubled over the observed 15 years. There has been a significant increase in precancerous lesions, which were found in approximately 50% of conizations. The total number of CC diagnosed by conization increased by 37.5% and the total of CIN3 increased by 130%. Age-standardized incidence of CC and CIN3 increased from 2.4 to 3.3/100,000 and from 11.6 to 26.9/100,000, respectively. The incidence of CC was lower in Central Switzerland compared to incidence in the Canton of Zurich and in Switzerland generally. Conclusion Approximately 50% of all conizations were performed on women without serious precancerous lesions. For this reason, we recommend the adaptation of screening modalities and the use of risk stratification to avoid overtreatment. In light of the forthcoming implementation of an HPV vaccination program, our data provides important baseline information.